Sex Disparity in the In-Hospital Outcomes of Patients with Kidney Disease Admitted for Myocardial Infarction: Insights from a Large National Database - Rivera, Frederick Berro (Archīum Ateneo, 2024)
Introduction There is limited evidence as to the effect of sex on the outcomes of patients admitted for ST-elevation myocardial infarction (STEMI) who have a concomitant diagnosis of chronic kidney disease (CKD) and end-stage renal disease (ESRD). We aimed to determine if there are differences in the outcomes between males and females in these patient populations. Methods Data were obtained from the National Inpatient Sample database and patients were selected using the International Classification of Diseases, Ninth and Tenth Revision (ICD-9 and -10) codes. Hospitalizations for patients with CKD who had STEMI from 2012 to 2020 were included. The primary outcome of interest was in-hospital mortality. Secondary outcomes evaluated included ischemic stroke, major bleeding complications, pressor requirement, permanent pacemaker implantation, percutaneous coronary intervention, coronary artery bypass grafting, surgery, pericardiocentesis, mechanical circulatory support, and mechanical ventilation. Results A total of 1,283,255 STEMI patients without CKD, 158,715 STEMI patients with CKD, and 22,690 STEMI patients with ESRD were identified and analyzed. Among patients with STEMI and CKD, females demonstrated higher in-hospital mortality compared to male counterparts (16.7% vs. 12.7%, aOR = 1.13, 95% CI: 1.05-1.21, p < 0.01). While there was no sex difference in the in-hospital mortality among STEMI patients with ESRD, female patients in this group were less likely to receive coronary artery bypass grafting and mechanical circulatory support. Conclusion Increased in-hospital mortality rates were shown for females admitted for STEMI with CKD. Among patients with ESRD who had STEMI, females were less likely to receive coronary artery bypass grafting and mechanical circulatory support. Further research needs to be conducted to better explain this said difference in outcomes.